Consumer Perception of B2C Websites : An Empirical Study of Delhi â€“ NCR - Agarwal, Sonali; Raychaudhuri, P. S. (Indian Journal of Marketing, 2019)
In the era of globalization, e - commerce is a great revolution. Online shopping through business to consumer websites is the use of the Internet for better marketing performance, and retailers are devising strategies to meet the demand of online shoppers ; they are busy in studying consumer behavior in the field of online shopping to see the consumer attitudes towards online shopping. We tried to check and modelize the change in frequency of online shopping visits with change in few characteristics and parameters of the business to consumer websites. It was found that frequency of online shopping and the number of visits to the websites increased with increase in content, variety, performance, security, and aesthetics of the websites. We established â€œSecurityâ€ of the website as the major factor of concern for online purchasers. Customers had high apprehensions and misgiving attitude for breach of security ethics. They did not like being directed to spam sites, spam advertisements, unwanted links, pop - ups , etc. A dislike for storing of personal information by the website also creates worry and uneasiness amongst the purchasers. Thus, we can say that in order to increase the online shopping frequency and satisfaction, the B2C websites will have to cater to these reasons of mistrust and redesign their websites for increased consumer buying. This research can be used by various e-marketers to improve product selling through various business to consumer websites.